The Antioxidant Activity Components Change of Pears Subject to Static and Dynamic Loads. (14th September 2020) - Azadbakht, Mohsen; Vahedi Torshizi, Mohammad
ABSTRACT: The present research investigated the effect of static and dynamic loading in various storage periods on the amounts of pears' components like total phenol content, DPPH radical scavenging activity, and Vitamin C amount. in this investigation was subjected to static loading (thin-edge and wide-edge compression) using three different force and for dynamic loading using three weights in three different storage periods. Next, the total phenol content, percentage of antioxidant activity and vitamin C were measured. The results showed that the total phenol content, DPPH radical scavenging activity, and vitamin C rates were decreased with increasing force and weight loading and also with increasing storage period the amount of components were decreased. The amount DPPH radical scavenging activity, phenol compound and vitamin-C for control sample were 54.36%, 32.5 mg GAE/100 g and 8.3 mg/100Fw respectively, Also for wide loading and thin loading this amount was 35.56 and 37.56%, 13.11 and 21.29 mg GAE/100 g and 5.76 and 6.33 mg/100Fw respectively, For dynamic loading was 25.015%, 11.37 mg GAE/100 g and 5.82 mg/100Fw respectively. In general, the highest amount for the total phenol content, DPPH radical scavenging activity, and vitamin C obtained in thin-edge loading, also the wide-edge and dynamic loading had more effect on decreasing phenol and vitamin-C in pear during storage.